Distribusi Barang dan Prosedur Cabang atas Pemenuhan Permintaan Pelanggan Goexpress - Prayogo Adjie Pangestu; Erni Pratiwi Perwitasari; Sumilah Sumilah (Institut Transportasi dan Logistik Trisakti, 2020)
The purpose of this study is to determine and analyze whether there is a positive influence on the distribution of goods and the implementation of Procedures on Consumer Demand for Brand Go Express at PT Aerojasa Cargo. The survey method was used as a way to collect primary data and distribute questionnaires to 30 respondents or Go Express customers as research samples. To solve the problem the author uses 2 (two) methods, namely, the forst method of collecting data in the form of questionnaires and library data. Both methods of data analysis using multiple linear regression analysis, correlation coefficient, determinant coeffient, and hypothesis testing. The results of the analysis partially have a positive and significant influence between the variables of Goods Distribution Service (X1) on Brand Go Express Customers Demand at PT Aerojasa Cargo Jakarta (Y). As far the variable implementation of Procedure Branch (X2) Against Customer Demand for Brand Go Express at PT Aerojasa Cargo Jakarta (Y). Based on the results of empirical evidence, it simultaneously shows that the variable Goods Distribution Service (X1) and application of Procedure Branch (X2) have a joint effect on Towards Brand Go Customer Request at PT Aerojasa Cargo Jakarta (Y).